Search for direct CP violation in singly Cabibbo-suppressed D± → K+K-π± decays - Lees, Jean-Pierre; Adametz, Aleksandra; Uwer, Ulrich (Physical review. D, Particles, fields, gravitation, and cosmology, 2013)
We report on a search for direct CP violation in the singly Cabibbo-suppressed decay D+→K+K−π+ using a data sample of 476 fb−1 of e+e− annihilation data accumulated with the BABAR detector at the SLAC PEP-II electron-positron collider, running at and just below the energy of the Υ(4S) resonance. The integrated CP-violating decay rate asymmetry ACP is determined to be (0.37±0.30±0.15)%. Model-independent and model-dependent Dalitz plot analysis techniques are used to search for CP-violating asymmetries in the various intermediate states. We find no evidence for CP-violation asymmetry.